2019
DOI: 10.1161/hypertensionaha.119.12780
|View full text |Cite
|
Sign up to set email alerts
|

Global REACH 2018

Abstract: Excessive erythrocytosis (EE; hemoglobin concentration [Hb] ≥21 g/dL in adult males) is associated with increased cardiovascular risk in highlander Andeans. We sought to quantify shear stress and assess endothelial function via flow-mediated dilation (FMD) in male Andeans with and without EE. We hypothesized that FMD would be impaired in Andeans with EE after accounting for shear stress and that FMD would improve after isovolemic hemodilution. Brachial artery shear stress and FMD were assessed in 23 male Andea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…The pathophysiology of HACE is reversible, and vasogenic brain edema leads to microbleeds. The collapse of the blood brain barrier due to vasodilation with increased cerebral blood flow under low oxygen pressure and high-altitude erythrocytosis causes unique distributions and distinct MRI findings ( 7 , 8 ). These structures are anatomically classified as white matter, which is more vulnerable to vasogenic brain edema in comparison to gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of HACE is reversible, and vasogenic brain edema leads to microbleeds. The collapse of the blood brain barrier due to vasodilation with increased cerebral blood flow under low oxygen pressure and high-altitude erythrocytosis causes unique distributions and distinct MRI findings ( 7 , 8 ). These structures are anatomically classified as white matter, which is more vulnerable to vasogenic brain edema in comparison to gray matter.…”
Section: Discussionmentioning
confidence: 99%
“…At 5100 m, blood viscosity measured at native haematocrit and at the two highest shear rates was higher in highlanders with moderate-to-severe CMS than in highlanders without CMS, suggesting that blood viscosity could also play a role in the development of CMS. A rise in blood viscosity has previously been observed in Andeans with EE (Tremblay et al 2019) but the relationship between CMS symptoms and blood viscosity has not yet been studied. Surprisingly, blood viscosity measured at the lower shear rate (i.e.…”
Section: Haemorheologymentioning
confidence: 99%
“…It is well known that remarkable alterations occur in hematology to accommodate the HAH condition (Berglund, 1992;Huang et al, 2017). Chronic HAH-induced excessive erythrocytosis increases the blood viscosity, leading to the increased risk of various cardiovascular disorders (e.g., hypertension, vascular thrombosis, and myocardial infarction; Lowe et al, 1997;Tremblay et al, 2019). Our hematological indices revealed that chronic HAH for 4 weeks increased the amounts of overall RBCs and hemoglobin as well as the volume percentage of RBCs in the blood.…”
Section: Discussionmentioning
confidence: 68%
“…Migrants ascending to high altitudes often suffer from acute mountain sickness with symptoms, like headache, insomnia, and fatigue (Hackett and Roach, 2001), while native or longtime dwellers at high altitudes have a high risk of developing chronic mountain sickness due to compensatory adaptation of organism to chronic HAH, and the risk is greater as the altitude increases (Azad et al, 2017). Exaggerated polycythemia represent the key characteristic of acclimation to chronic HAH, which is associated with increased blood viscosity and blood volume (León-Velarde and Richalet, 2006;Tremblay et al, 2019). Long-term HAH exposure also results in pulmonary hypertension with increased pulmonary vascular resistance due to pulmonary vasoconstriction and vascular remodeling (Penaloza and Arias-Stella, 2007).…”
Section: Introductionmentioning
confidence: 99%